IPTEK PENGAMANAN KAWASAN MESJID DESA MENGGUNAKAN PERANGKAT LUNAK CCTV DAN PENERANGAN BERBASIS LISTRIK TENAGA SURYA - Dalimunthe, Afifuddin; Fauzia, Lily; Utomo, Budi (Unri Conference Series: Community Engagement, 2024)
Tuntungan II Village is quite close to the original university, namely Universitas Sumatera Utara, which is only 15 km away. This area is currently the target area for community services activities because it is related to the rise in criminal activity in this village. This is related to the increasing difficulty for residents to obtain work. The Al Ikhlas Mosque, which is located in this village, is a mosque that was only built in the last 3 years with community self- funding and involving donations from various parties. Currently, this mosque can function as a means of large-scale congregational prayers such as Friday prayers, etc. However, due to limited funds, many facilities have not yet been met. Among these are security support facilities. Due to the limitations faced by residents, this mosque has minimal lighting and does not have its own security guard when residents perform their prayers. As a result, residents often complain about the frequent loss of motorbikes and other valuables. The entry of the community services team into this area is a breath of fresh air to answer the need for worship facilities. Now, with the installation of 8 channel closed circuit television (CCTV) with a 43inch flat television and lighting around the mosque area with 6 solar power plant-based public street lighting, it provides security and comfort for residents who worship. Losing your vehicle and shoes/sandals is now unheard of.